The social sciences empowered : proceedings of th 7th International Congress on Interdisciplinary Behavior and Social Sciences 2018 (ICIBSOS 2018), 21-22 July, Bangkok, Thailand, 22-23 September, Bali, Indonesia, 6-7 October, Bali, Indonesia, 24-25 November 2018, Yogyakarta, Indonesia - Gaol, Ford Lumban; Hutagalung, Fonny; Chew, Fong Peng (CRCPress/Balkema, 2020)
"ICIBSoS 2018 provided the economic and social analysis necessary for addressing issues in Humanities disciplines such as Education, Sociology, Anthropology, Politics, History, Philosophy, Psychology as well as food security. Contributions to these proceedings give necessary insight into the cultural and human dimension of such diverse research areas as transport, climate change, energy and agriculture. It proposes new ideas, strategies and governance structures for overcoming the crisis from a global perspective, innovating the public sector and business models, promoting social innovation and fostering creativity in the development of services and product design"- Resumé vydavatel
Keywords: společenské vědy; social sciences; elektronické knihy; sborníky konferencí; electronic books; proceedings of conferences